(untitled) (Journal of Philosophy Culture and Political Science, 2015)
The «female history» described in a written monument of medieval Turkic culture «The book of my grandfather Korkud» is given in the article. Alongside with history of wars and attacks of sultans and leaders of tribes of oguz «The female history» is represented in it as well. The image of the powerful maiden, known in the powerful fairy tale and the heroic epos, is represented as a female ideal of the nomadic and semi-nomadic Turkic people. The evolution of a female image reflected in legends, legends and myths of the Turkic people is traced in the article. Archaism of a female image of ancient stories of the Turkic people is emphasized in this publication. Realistic character of a female ideal of the epos of Turkic peoples at the time of the storyteller’ life and musician – Korkut-At is traced in the article on materials of the epos of oguz, historical sources and scientific publications. The female ideal of the epos of oguz is caused by a way of life of Turkic peoples in which war was «honourable occupation», «some kind of sport», this fact is noted in the article.